2014
DOI: 10.1161/jaha.113.000689
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Arteriovenous Shunt Occlusion Using Microbubble and Ultrasound Mediated Thromboprophylaxis

Abstract: BackgroundPalliative shunts in congenital heart disease patients are vulnerable to thrombotic occlusion. High mechanical index (MI) impulses from a modified diagnostic ultrasound (US) transducer during a systemic microbubble (MB) infusion have been used to dissolve intravascular thrombi without anticoagulation, and we sought to determine whether this technique could be used prophylactically to reduce thrombus burden and prevent occlusion of surgically placed extracardiac shunts.Methods and ResultsHeparin‐bonde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that microbubbles increase the possibility of acoustic cavitation and cavitation-related vascular damage effects, such as microvascular rupture and petechial hemorrhage (Miller and Gies, 2000a ; Miller and Quddus, 2000b ; Miller, 2007 ), in which microbubbles served as cavitation nuclei to induce cavitation (Miller and Thomas, 1995 ). These vascular effects could be therapeutically useful in thrombolysis and gene or drug delivery (Molina et al, 2006 ; Ferrara et al, 2007 ; Xie et al, 2009 ; Kutty et al, 2014 ; Sato et al, 2015 ; Burgess and Hynynen, 2016 ). Recently, some studies showed that the permeability of the BTB is increased by focused ultrasound and low-frequency ultrasound in the presence of an ultrasound contrast agent (Liu et al, 2006 ; Hynynen, 2008 ; Xia et al, 2012 ; Diaz et al, 2014 ; Aryal et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that microbubbles increase the possibility of acoustic cavitation and cavitation-related vascular damage effects, such as microvascular rupture and petechial hemorrhage (Miller and Gies, 2000a ; Miller and Quddus, 2000b ; Miller, 2007 ), in which microbubbles served as cavitation nuclei to induce cavitation (Miller and Thomas, 1995 ). These vascular effects could be therapeutically useful in thrombolysis and gene or drug delivery (Molina et al, 2006 ; Ferrara et al, 2007 ; Xie et al, 2009 ; Kutty et al, 2014 ; Sato et al, 2015 ; Burgess and Hynynen, 2016 ). Recently, some studies showed that the permeability of the BTB is increased by focused ultrasound and low-frequency ultrasound in the presence of an ultrasound contrast agent (Liu et al, 2006 ; Hynynen, 2008 ; Xia et al, 2012 ; Diaz et al, 2014 ; Aryal et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Guided high mechanical index (MI) impulses from a diagnostic US system during intravenous microbubble (MB) infusion have the potential to dissolve intravascular thrombi (termed sonothrombolysis) without the need for fibrinolytic therapy. We have previously studied the feasibility of treating deeply located acute intravascular thrombi with US and intravenous MBs 17 , 18 , 19 . The spasm reversal properties of US + systemic MB therapy have not been previously investigated, but diagnostic US-induced MB cavitation has been shown to enhance endothelial nitric oxide (NO) release 20 , 21 .…”
mentioning
confidence: 99%